Working with PREVENT: Social Work Options for Cases of 'Radicalisation Risk'. Issue 2 (15th March 2018) - Stanley, Tony; Guru, Surinder; Gupta, Anna
Abstract : 'Radicalisation risk' and the associated practice and organisational responses to it are accepted, rather uncritically, as legitimate activity for statutory social workers. Yet, the policy backdrop driving much of this development has not been matched by practice debate or learning about how best to work with these cases. The 2015 PREVENT Duty mandates social workers and many other practitioners 'to pay due regard' to possible radicalisation concerns, without offering practical or ethical ways to do so. This paper attends to that gap, and brings together learning from a series of practitioner events and draws on strengths-based approaches to offer practical ways forward. By doing this, the paper offers practice guidance to this growing area of work. Occupational and professional paradigm differences emerged as an issue for the workers we talked to, and this is discussed. Moving beyond the dichotomous and divisive debate of the PREVENT Duty as 'good or bad', and about its legitimacy as a concern for social work, we take a pragmatic approach to show how social workers can operate ethically and co-operatively within it, importantly because presently they must do so.